Pengobatan Gratis ( Kadar Gula Darah,Asam Urat ) Untuk Lansia Di Desa Aek Godang Laru Kec. Panyabungan Kab. Mandailing Natal - Helmi Wardah Nasution; Ferika Desi; Khoirunnisaa Batubara; Dewi Sri Rahayu Tinendung (Cattleya Darmaya Fortuna, 2024)
Prediabetes is subject with increased plasma glucose level but not high enough to reach minimal level for criteria of diabetes mellitus diagnosis. Prediabetes criteria are those who classified as Impaired Fasting Blood Glucose (IFBG) and Impaired Glucose Tolerance (IGT) with Fasting Glucose of 100-125 mg/ dl and 2-hours postprandial glucose of 140-190 mg/dl. The method was conducted by using analytical observational with cross sectional approach. Instruments used in this study were UASure Blood Uric Meter to examine uric acid level and glucoSure Blood Glucose Meter to examine blood glucose level. The results of this study tested with Spearman’s correlation test which showed p value = 0,008, because p value was less than or equal to α (0,05) therefore Ho was rejected and H1 was accepted. There was significant association between uric acid level and blood glucose level in prediabetes women. The increase of blood glucose level was in line with uric acid level.